A Stepwise Approach Using Metastatic Lymph Node Ratio-Combined Thyroglobulin for Customization of [(18)F]FDG-PET/CT Indication to Detect Persistent Disease in Patients with Papillary Thyroid Cancer - Piao, Hong Hua (Diagnostics (Basel), 2021)
We investigated whether an indication for [(18)F]FDG-PET/CT to detect FDG-avid persistent disease (PD) could be identified precisely using the extent of metastatic lymph nodes (MLNs) and serum thyroglobulin (Tg) in papillary thyroid cancer (PTC) patients. This retrospective study included 429 PTC patients who underwent surgery and radioactive iodine (RAI) therapy. [(18)F]FDG-PET/CT and serum Tg were evaluated just before RAI therapy. The MLN ratio (LNR) was defined as the ratio of the number of MLNs to the number of removed LNs. To derive the LNR-combined criteria, different Tg cut-off values for identifying the PET/CT-indicated group for PD detection were applied individually to subgroups initially classified based on LNR cut-off values. The cut-off values for serum Tg, the number of MLNs, and LNR for a PET/CT indication were 6.0 ng/mL, 5, and 0.51, respectively. Compared to a single parameter (serum Tg, total number of MLNs, and LNR), the LNR-combined criteria showed significantly superior diagnostic performance in detecting FDG-avid PD (p < 0.001). The diagnostic performance of PET/CT in detecting FDG-avid PD was significantly improved when the PET/CT-indicated group was identified through the LNR-combined criteria in a stepwise manner; this can contribute to a customized PET/CT indication in PTC patients.